Applying Partial Least Squares in Tourism and Hospitality Research 2018
DOI: 10.1108/978-1-78756-699-620181002
|View full text |Cite
|
Sign up to set email alerts
|

New Guidelines for the Use of PLS Path Modeling in Hospitality, Travel, and Tourism Research

Abstract: No part of this book may be reproduced, stored in a retrieval system, transmitted in any form or by any means electronic, mechanical, photocopying, recording or otherwise without either the prior written permission of the publisher or a licence permitting restricted copying issued in the UK by The Copyright Licensing Agency and in the USA by The Copyright Clearance Center. Any opinions expressed in the chapters are those of the authors. Whilst Emerald makes every effort to ensure the quality and accuracy of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 152 publications
0
26
0
Order By: Relevance
“…In accordance with the literature (Chin et al, 2003; Fassott, Henseler, & Coelho, 2016), PLS‐SEM is superior to covariance‐based SEM when a product indicator approach for modeling interactions is employed. Third, PLS‐PM has also become a popular statistical method in the field of tourism and hospitality research (Henseler, Müller, & Schuberth, 2018). A review of the use of PLS‐SEM in hospitality research suggested that this approach was particularly suitable for running complex structural relationships and moderation analyses (Ali, Rasoolimanesh, Sarstedt, Ringle, & Ryu, 2018).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…In accordance with the literature (Chin et al, 2003; Fassott, Henseler, & Coelho, 2016), PLS‐SEM is superior to covariance‐based SEM when a product indicator approach for modeling interactions is employed. Third, PLS‐PM has also become a popular statistical method in the field of tourism and hospitality research (Henseler, Müller, & Schuberth, 2018). A review of the use of PLS‐SEM in hospitality research suggested that this approach was particularly suitable for running complex structural relationships and moderation analyses (Ali, Rasoolimanesh, Sarstedt, Ringle, & Ryu, 2018).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…In terms of data analysis, it is proposed a variancebased structural equation modelling (SEM), PLS, aiming to apply to the proposed casual confirmatory research model [27] and, this way, verifying the suggested hypothesis. This research follows a four-step design with the aim of analysing and understanding the PLS results [28].…”
Section: Methodsmentioning
confidence: 99%
“…For the confirmatory analysis (reliability and validity) of the scale, we opted for the partial least squares path modelling (PLS-PM). The choice of PLS-PM also known as the PLS-SEM method (Ali et al, 2018;Henseler et al, 2018;Sarstedt et al, 2020) was justified by the reflexive nature of our constructs and the fact that our measurement model was still in development.…”
Section: Measurement Scale In the Context Of Hospitalitymentioning
confidence: 99%